RISK MANAGEMENT ACCORDING TO THE REQUIREMENTS OF THE STANDARD ISO 31000 AND 9001: 2008 IN A VETERINARY INSTITUTE - Vukašinović, Marija; Vukašinović, Jovan; Vukašinović, Ana; Obradović, Saša; Debeljak, Zoran (Economics of Agriculture, 2011)
The introduction and application of the revised 9001:2008 standard resulted in the discussion among quality managers about the need to perform risk assessment and the volume of the performance. This led to conflicting opinions as few people focused on interpretation and intentions of the standard regardless of where it was applied- in production organizations or in those that sell services. This paper points out not only the importance of risk assessment but risk management too as a precondition for safer business operations of the Specialized Veterinary Institute Kraljevo" (VSI) from Kraljevo in its environment.